The Symphonic Poem of Levko Kolodub «Velykyi Kameniar» («The Big Stonemason»): Contexts of Musical Embodiment - Sikorska, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
Introduction. Levko Kolodub — is one of the most outstanding Ukrainian composers of the 2nd half of the XXth — the beginning of the XXIth century. He is the author of a huge number of symphonic works (including thirteen symphonies, and also poems, rhapsodes, suites, and so on. Studying his creative work will never lose its actuality in the context of understanding the integrity, depth, and diversity of our national musical culture. The relevance of the study. In 2023 it was the 70th anniversary of Levko Kolodub’s first large-scale opus — the symphonic poem “The Great Stonemason”, which he wrote in 1953. Aidar Torybayev, a famous Ukrainian conductor of Kazakh origin opened the new 2023/2024 concert season of the Dnipropetrovsk Philharmonic with this piece. After he received numerous requests from his colleagues for the score, he decided to print it. That made the study of the symphonic poem “The Great Stonemason” necessary. Until now There was no comprehensive study of this composition. So, the concert practice actualized a musicologist studying as well. The main objective of the study — is a musicological presentation of this poem in a wide contextual field, which sets us several tasks, namely: to consider the contexts of the work, the history of its writing, its place in the symphonic heritage of L. Kolodub; to discover the genre model of the poem along, with its distinctive and innovative features of “The Stonemason” as genre invariant of a symphonic poem, stylistic features. The methodology includes methods: biographical (to reconstruct the facts of life, the periods of L. Kolodub’s life — childhood and education, related to the poem); historical (to highlight the context of the work), comparative (to reveal the heredity of the Poem about previous examples of the genre), structural and functional, genre-stylistic and intonation-dramaturgical methods (for a comprehensive analysis of the work), source studies (study of epistolary fragments), interviewing with A. Torybyaev (September-October 2023) to clarify the performance and interpretation features of the work. Results and conclusions. As a result of our research, we concluded that Levko Kolodub in his first composition of a large form showed exceptional talent despite his young age. He demonstrated excellent composition skills, a well-formed style, professional expertise, and a constant desire for improvement. “The Great Stonemason” followed the established traditions of the romantic poem genre, with F. Liszt’s poems serving as a stylistic model. These traditions included the use of the principle of monothematism in constructing various themes, the sonata form with a contrasting introduction, the hidden cyclicality within the one-part form, etc. The piece was both unique and personal, vividly individual: with themes, inspired by folklore, featuring characteristically scaled harmony, and a requiem episode in its development, etc. it was one of the several similar works from that time, alongside those by Anatoliy Svechnykov, Volodymyr Nakhabin, Andriy Shtoharenko, and others, that glorified national heroes, love for the Motherland, etc. The composer carried the desire for symphonic music and programming throughout his long life. The analyzed poem utilized folkloric principles such as intonation, mode, metrorhythm, etc. The composer employed various techniques such as dramatic conflict within the sonata-allegro, tense development episodes, gradual dynamic growths and declines, numerous polyphonic methods of instrumental and vocal nature, dynamic reprise, etc. These features were crucial for the composer’s further development as an artist. The symphonic poem «The Great Stonemason» continues an active creative life due to its engaging performance. Therefore, we ensure, that introducing this work into scientific circulation has a promising future.